Nutritional and hygienic quality of meals served in school canteens in Togo - Mizehoun-Adissoda, Carmelle; ADJOBIMEY, M; YEMOA, Loconon Y. Achille (My University, 2021)
School feeding is important in terms of nutrition, as it contributes to the prevention of malnutrition, especially in low-income countries. However, the nutritional and hygienic quality of meals served at schools in several countries is rarely examined. We aimed to assess the quality of meals served in school canteens in Togo. We designed a descriptive cross-sectional study and collected data from eight school canteens located in Southern Togo. Hygiene compliance and potential sources of food contamination in the canteens were assessed using the 5 M approach, which evaluates the performance of hygiene parameters at each “M" i.e., medium (cooking environment), raw material (staples), cooking material (kitchenware), method (cooking) and manipulator (cooks) in the food preparation environment. Foods were sampled in each school and analysed for microbiological (presence of Salmonella, total coliforms, and staphylococci) and nutritional (nutrient content) quality. The 5 M analysis revealed significant hygienic violations by the food preparators, as well as poor preparation conditions and utilization of low-quality raw materials in all the school canteens. Out of the 30 meal samples collected, 10 were of poor microbiological quality with the presence of total coliforms and staphylococci exceeding established limits of 10 and 100 cfu/g in 30 and 6.6% of the meals, respectively. However, none of the meals was contaminated by Salmonella spp. Nutritional analysis revealed that none of the meals served respected the nutritional balance, especially for contents in calcium, and vitamins A and C. Nonetheless, the iron content complied with the recommendations for children aged 9–13 years. Our analyses showed that several routes of contamination exist for the meals consumed in school canteens in Togo. Also, the nutritional quality of the ready- to-eat foods served at school canteens needs to be improved, particularly with the inclusion in the diet of fruits and vegetables to cover the micronutrient requirements.
Keywords: School feeding; Hygiene; Food quality; Nutrition